2020
DOI: 10.1007/s15010-020-01548-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher viral loads in asymptomatic COVID-19 patients might be the invisible part of the iceberg

Abstract: Purpose SARS-CoV-2 virus dynamics in different hosts and different samples and their relationship with disease severity have not been clearly revealed. The aim of this study is to evaluate the viral loads of 6 different sample types (nasopharyngeal/ oropharyngeal combined, oral cavity, saliva, rectal, urine, and blood) of patients with different ages and clinics, to reveal the relationship between disease course and SARS-CoV-2 viral load, and differences in viral loads of asymptomatic and symptomatic patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
113
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 25 publications
10
113
1
2
Order By: Relevance
“…Elderly and female groups are con rmed to have higher frequencies of SARS-CoV-2 infection, thus age and gender could be considered important risk factors, as already described by other authors [5-18-27]. A non-negligible percentage of positive individuals (29.7%) showed an asymptomatic clinical course, moreover, median viral loads resulted to be statistically signi cant when compared to symptomatic ones, corroborating other authors' ndings [5]. These observations could suggest their possible role in viral circulation inside the nurseries.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Elderly and female groups are con rmed to have higher frequencies of SARS-CoV-2 infection, thus age and gender could be considered important risk factors, as already described by other authors [5-18-27]. A non-negligible percentage of positive individuals (29.7%) showed an asymptomatic clinical course, moreover, median viral loads resulted to be statistically signi cant when compared to symptomatic ones, corroborating other authors' ndings [5]. These observations could suggest their possible role in viral circulation inside the nurseries.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, elderly people are supposed to be particularly susceptible to the infection, especially in age class over 65 years [9-18-27]. The role of asymptomatic as a possible super spreader is unclear, in fact some authors has described various scenarios in which the viral load is higher in symptomatic elderly people [6-11-13, 17-27] instead of other cases where these ndings were observed in asymptomatic ones [5], that nds accordance with Ra et al which found that asymptomatic individuals showed persistent positive upper respiratory traits [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations